(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Stress and well being are the two important key aspects of the mental health. Objective: impact of mindfulness meditation on perceived stress levels and subjective well- being Methods: The quasi-experimental research design was used for the present study without randomization. Participants in the first phase had undertaken baseline pre-test evaluation by using two standardized scales, perceived stress scale (PSS) and subjective well -being inventory (SUBI). The experimental group learnt about mindfulness meditation for a month (20 minutes each day), while the control group received no interventions. After a one-month intervention, a post-test was conducted by using similar standardized tools. Results: In correlation results, post- stress and post- wellbeing, the r-value was found to be -.457** and the (p=<0.001) which was significant at 0.05 level of significance, and hence, negative moderate correlation exist between perceived stress and subjective well-being in experimental group. Perceived stress and subjective well-being are inversely proportional to each other. Conclusion: Mindfulness meditation reduced the perceived stress score and improved the subjective well- being score among participants.